2014
DOI: 10.1002/glia.22647
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ produced by IL‐10 redirected astrocytes attenuates microglial activation

Abstract: While there clearly is an intimate relationship between astrocytes and microglia, few studies have examined these potentially dynamic interactions. In this study, cytokine-mediated communication between microglia and astrocytes under inflammatory conditions was investigated. We have previously shown that activated microglia produce Interleukin (IL)-10, a regulatory cytokine that plays an important role in resolving neuroinflammation. Nonetheless, the mechanism by which IL-10 attenuates pro-inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
210
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(236 citation statements)
references
References 56 publications
(86 reference statements)
13
210
1
Order By: Relevance
“…Other studies have demonstrated that after IPC, astrocytes upregulate 14-3-3γ [102,103], a multifunctional scaffolding protein, and alleviate energy depletion through different pathways [102]. Ischemia induces a cellular redistribution of astrocytic gap junction proteins, including Cx34 [104,105]. Cx34-expressing astrocytes have been found in the peri-infarct region of the poststroke brain [104], where they may secrete growth factors that promote neuronal survival and stimulate angiogenesis in infarcted tissue [105][106][107].…”
Section: Astrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have demonstrated that after IPC, astrocytes upregulate 14-3-3γ [102,103], a multifunctional scaffolding protein, and alleviate energy depletion through different pathways [102]. Ischemia induces a cellular redistribution of astrocytic gap junction proteins, including Cx34 [104,105]. Cx34-expressing astrocytes have been found in the peri-infarct region of the poststroke brain [104], where they may secrete growth factors that promote neuronal survival and stimulate angiogenesis in infarcted tissue [105][106][107].…”
Section: Astrocytesmentioning
confidence: 99%
“…Ischemia induces a cellular redistribution of astrocytic gap junction proteins, including Cx34 [104,105]. Cx34-expressing astrocytes have been found in the peri-infarct region of the poststroke brain [104], where they may secrete growth factors that promote neuronal survival and stimulate angiogenesis in infarcted tissue [105][106][107].…”
Section: Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a time course study of responses to peripheral LPS challenge, Norden et al [20] found that microglia are activated first, followed by astrocytes. Furthermore, microglial IL-10 stimulates astrocytic TGF-β in response to LPS challenge [27]. The large overlap between molecular pathways activated in response to LPS and ischemia is, in part, responsible for the phenomenon of crosstolerance (discussed previously), suggesting that IPC may modulate microglia/astrocyte interplay, with both cells playing important roles in conferring IPC-mediated neuroprotection.…”
Section: Astrocytesmentioning
confidence: 87%
“…The shared modulation of neuroimmune components appears to be responsible for the overlap in neuroprotection offered against ischemia by multiple preconditioning stimuli. [19,20], microglia [20], peripheral immune cells [19][20][21] HIF-1 Regulates metabolic genes to protect against hypoxia Multiple CNS cells [17,22], peripheral immune cells [23] Type TLRs Reprograms cellular genomic response to ischemia Circulating leukocytes [16], endothelial cells [16], microglia [17,18] TGF-β Promotes repair of neurovascular unit, regulates immune system function Astrocytes [20,27], microglia [27], T cells [28] TLR = Toll-like receptor; TNF = tumor necrosis factor; NFkB = nuclear factor kB; CNS = central nervous system; HIF = hypoxia-inducible factor; IFN = interferon; IRF = IFN regulatory factor; TGF = transforming growth factor…”
Section: Cross-tolerancementioning
confidence: 99%